2016
DOI: 10.1055/s-0042-119649
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of LAMP2 in Coronary Artery Disease: Association with Serum Lipid Profile

Abstract: Whereas several in vitro and in vivo studies have described the role of lysosomal associated membrane protein 2 (LAMP2) in lipid homeostasis, there is no study addressing LAMP2 serum concentration and its association with lipid profiles in the context of coronary artery disease (CAD). We aimed to determine the LAMP2 serum concentration and its association with serum lipid profiles as well as the gene expression of LAMP2 in peripheral blood mononuclear cells (PBMCs) of CAD patients and control group. Circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Patients with coronary artery disease showed an upregulation of LAMP2 expression in peripheral blood mononuclear cells when compared with the control group. The collected data revealed a role for LAMP2 in lipid homeostasis and coronary artery disease development [57]. Atherosclerosis progression is accelerated in NEIL3-deficient individuals via activation of the Akt signaling pathway and other non-canonical processes impacting the phenotype of vascular smooth muscle cells [58].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with coronary artery disease showed an upregulation of LAMP2 expression in peripheral blood mononuclear cells when compared with the control group. The collected data revealed a role for LAMP2 in lipid homeostasis and coronary artery disease development [57]. Atherosclerosis progression is accelerated in NEIL3-deficient individuals via activation of the Akt signaling pathway and other non-canonical processes impacting the phenotype of vascular smooth muscle cells [58].…”
Section: Discussionmentioning
confidence: 99%
“…There is almost no change in glucose metabolism under normal dietary feeding, but LAMP2 KO mice show poor resistance to obesity caused by a HFD, high insulin hyperglycemia and tissue lipid accumulation, accompanied by higher energy expenditure 72 . In coronary atherosclerosis disease, it has been found that the serum concentration of LAMP2 is positively correlated with LDL‐C, and the increased level of LAMP2 in the tissues (which may be reflected by the increased release of LAMP2 in the serum) may cause LDL‐C uptake, factors which reduce and increase serum LDL‐C levels 72,73 …”
Section: Lmps and Lipid Metabolismmentioning
confidence: 99%
“…72 In coronary atherosclerosis disease, it has been found that the serum concentration of LAMP2 is positively correlated with LDL-C, and the increased level of LAMP2 in the tissues (which may be reflected by the increased release of LAMP2 in the serum) may cause LDL-C uptake, factors which reduce and increase serum LDL-C levels. 72,73…”
Section: Lmps and Abnormalities Of Lipid Regulationmentioning
confidence: 99%